Clinical and therapeutic profile of patients insid with ulcers of inferior members: Clinical and therapeutic profile of patients insid with ulcers of inferior members - Peixôto Júnior, Antônio Belmiro (2020)
Objective: To describe the sociodemographic and clinical profile of patients admitted with lower limb ulcers in a teaching hospital; identify the main clinical and surgical procedures performed to treat these patients and relate the risk factors and complications found in these wounds. Method: This is a documentary-descriptive research with a quantitative approach, developed in a teaching hospital, in the city of Campina Grande-PB, through the analysis of medical records of patients who were hospitalized in medical clinics, in June 2012 to March 2017. Inclusion criteria were medical records with patients over 18 years and with lower limb ulcers. Results: The population included 168 medical records, of which only 53 served for analysis. Data were analyzed using descriptive and inferential statistics by Fisher's Exact Test. Conclusion: The average age was 61.55 years, most participants were men, brown, married, with incomplete elementary school, retired and hypertensive. Drugs were used in 100% of the patients and significant in the association of overweight complications with necrosis (0.044), sex with odor (0.043) and race with amputation (0.040). It is hoped that the present research will serve as a guide for other researchers and for better assistance.